2013
DOI: 10.1016/j.infbeh.2013.03.007
|View full text |Cite
|
Sign up to set email alerts
|

Measuring spatial proximity in mother–infant interaction: A kinematic approach for an examination of the effects of maternal postpartum depression

Abstract: This article appeared in a journal published by Elsevier. The attached copy is furnished to the author for internal non-commercial research and education use, including for instruction at the authors institution and sharing with colleagues.Other uses, including reproduction and distribution, or selling or licensing copies, or posting to personal, institutional or third party websites are prohibited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Depressed mothers may show a number of forms of disrupted interaction with their infants, such as intrusive, abrupt, or controlling actions and gestures, displays of negative affect (or less positive affect), the absence of timely or appropriate responses to infant cues, and/or failure to facilitate infant arousal regulation or to engage the infant in interaction (for reviews see Bernard, Nissim, Vaccaro, Harris, & Lindhiem, ; Field, ; Lovejoy, Graczyk, Ohare, & Neuman, ). Elevated maternal depressive symptoms have been associated with reduced responsiveness and sensitivity (Bernard et al, ; Stanley, Murray, & Stein, ), less frequent and affectionate physical touch (Ferber, Feldman, & Makhoul, ; Field et al, ), more difficulty regulating emotions (e.g., Riva Crugnola et al, ), less responsive speech (e.g., Murray, Kempton, Woolgar, & Hooper, ; Shannon & Leider, ), fewer verbal references to their infants' behavior (e.g., Herrera, Reissland, & Shepherd, ; Kaplan, Bachorowski, & Zarlengo‐Strouse, ), less smiling (e.g., Field et al, ), greater physical distance during interaction (Vaever, Krogh, Smith‐Nielsen, Harder, & Køppe, ), and more negative and intrusive behavior (Lyons‐Ruth, Connell, Grunebaum, & Botein, ; Tronick & Reck, ; for reviews see Bernard et al, ; Field, ; Lovejoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Depressed mothers may show a number of forms of disrupted interaction with their infants, such as intrusive, abrupt, or controlling actions and gestures, displays of negative affect (or less positive affect), the absence of timely or appropriate responses to infant cues, and/or failure to facilitate infant arousal regulation or to engage the infant in interaction (for reviews see Bernard, Nissim, Vaccaro, Harris, & Lindhiem, ; Field, ; Lovejoy, Graczyk, Ohare, & Neuman, ). Elevated maternal depressive symptoms have been associated with reduced responsiveness and sensitivity (Bernard et al, ; Stanley, Murray, & Stein, ), less frequent and affectionate physical touch (Ferber, Feldman, & Makhoul, ; Field et al, ), more difficulty regulating emotions (e.g., Riva Crugnola et al, ), less responsive speech (e.g., Murray, Kempton, Woolgar, & Hooper, ; Shannon & Leider, ), fewer verbal references to their infants' behavior (e.g., Herrera, Reissland, & Shepherd, ; Kaplan, Bachorowski, & Zarlengo‐Strouse, ), less smiling (e.g., Field et al, ), greater physical distance during interaction (Vaever, Krogh, Smith‐Nielsen, Harder, & Køppe, ), and more negative and intrusive behavior (Lyons‐Ruth, Connell, Grunebaum, & Botein, ; Tronick & Reck, ; for reviews see Bernard et al, ; Field, ; Lovejoy et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible pathway involves the oxytocinergic (OT) system, which underpins the capacity to form affiliative bonds, read social signals, and function competently within the social world, abilities compromised in children of depressed mothers . In this study, we use a well‐selected birth cohort of mothers who were repeatedly assessed for depression from birth and up to the child's sixth year of life to test associations between OT functionality of mother and child and observed mother–child interactions, which are known to be disrupted in cases of PPD …”
Section: Introductionmentioning
confidence: 99%
“…[3,10] In this study, we use a well-selected birth cohort of mothers who were repeatedly assessed for depression from birth and up to the child's sixth year of life to test associations between OT functionality of mother and child and observed mother-child interactions, which are known to be disrupted in cases of PPD. [11][12][13][14] The child's OT system develops in the context of the mother-infant bond and is shaped by parental OT and early caregiving experiences. [15,16] Studies across mammalian species have shown that maternal behavior during the sensitive postpartum period, including licking and grooming in rodents, [17] grooming and touch in primates, [18] and well-adapted synchronous parenting in humans, [19,20] shapes the infant's brain OT and peripheral OT response.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for the reduced activity may be that infants of depressed mothers adopt the depressed behavior of their mothers (Field et al., ); at the same time, the reduced gaze activity may also reflect a reduced level of activity in the mothers. A recent study within our sample showed that mothers with PPD tended to move less when interacting with their infants, probably due to psychomotor retardation being a core symptom in depression (Væver, Krogh, Smith‐Nielsen, Harder, & Køppe, ). A possible effect of this could be a reduced level of gaze activity in the infant because if the mother is less active, the infant does not have to be that active either in visually responding to her speech and movements.…”
Section: Discussionmentioning
confidence: 75%